2022
DOI: 10.1016/j.jobcr.2021.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of maxillofacial fractures in a Tertiary Referral Centre in Central Kerala - A comparison between the Pre-COVID and COVID periods

Abstract: Our aim was to observe if there was any appreciable difference in the etiology and pattern of maxillofacial fractures during the pre-COVID-19 and COVID-19 periods in Central Kerala, South India. This retrospective study was conducted with data over a period of two years from the central database registry of our hospital. Age, sex, etiology, date of injury, and site of facial fractures were recorded and compared between both the time periods. Increase in facial fractures due to fall at home (p value < 0.01) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
(8 reference statements)
2
6
0
Order By: Relevance
“…In our study, most of the injuries reported due to RTAs, have common presentation with fractured mandible or lower jaw (13). Mandibular fractures account for 57.2% of maxillofacial injuries followed by zygomatic bone, which is consistent with previous findings (14).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, most of the injuries reported due to RTAs, have common presentation with fractured mandible or lower jaw (13). Mandibular fractures account for 57.2% of maxillofacial injuries followed by zygomatic bone, which is consistent with previous findings (14).…”
Section: Discussionsupporting
confidence: 92%
“…As a consequence of this management, an important decrease in maxillofacial trauma in terms of incidence has been widely reported and described in international literature. [1][2][3][4][5] Moreover, elective surgery, and with it also maxillofacial one, has been gradually reduced nationwide in order to keep services operational without putting both healthcare professionals and patients at risk despite the assistance activity relating to traumatology and oncology has been guaranteed. [6][7][8] The purpose of this retrospective study is to analyze the management of maxillofacial trauma during the COVID-19 pandemic period at ''San Salvatore Hospital'' of L'Aquila and compare results with two different two-year periods, respectively, 2015-2016; 2017-2018 focusing our attention on incidence, age, gender, and etiology.…”
mentioning
confidence: 99%
“…These last measures have not only affected Italy but most of the nations in the world. As a consequence of this management, an important decrease in maxillofacial trauma in terms of incidence has been widely reported and described in international literature 1–5 . Moreover, elective surgery, and with it also maxillofacial one, has been gradually reduced nationwide in order to keep services operational without putting both healthcare professionals and patients at risk despite the assistance activity relating to traumatology and oncology has been guaranteed 6–8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…False negatives due to SARS-CoV-2 mutations, or poor collection, transport, or handling are also possible [ 11 ]. After reviewing the literature, we found that many other studies monotonously focused on facial trauma epidemiology during the pandemic [ 20 , 21 , 22 , 23 , 24 ]. To the best of our knowledge, this is the first case–control study concerning SARS-CoV-2-OSC in asymptomatic COVID-19 patients with OWF-PNS.…”
Section: Discussionmentioning
confidence: 99%